2021
DOI: 10.1007/s11262-021-01866-5
|View full text |Cite
|
Sign up to set email alerts
|

A SARS-CoV-2 mutant from B.1.258 lineage with ∆H69/∆V70 deletion in the Spike protein circulating in Central Europe in the fall 2020

Abstract: SARS-CoV-2 mutants carrying the ∆H69/∆V70 deletion in the amino-terminal domain of the Spike protein emerged independently in at least six lineages of the virus (namely, B.1.1.7, B.1.1.298, B.1.160, B.1.177, B.1.258, B.1.375). We analyzed SARS-CoV-2 samples collected from various regions of Slovakia between November and December 2020 that were presumed to contain B.1.1.7 variant due to drop-out of the Spike gene target in an RT-qPCR test caused by this deletion. Sequencing of these samples revealed that althou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Analysis of the results obtained with specimens of the B.1.1.7 lineage always revealed a notable difference between the Cq values for the N and S genes (mean, + 11 ±2; range, + 8/ + 15), while such a difference was not observed with specimens of the other lineages ( Table 1 ). The Taq-Path COVID-19 RT-PCR assay revealed a missing S-gene target amplification with all specimens of VOC-UK, but also with B.1.258 ( Table 1 ), as expected from the presence of the HV69-70 spike deletion also in members of this lineage ( Brejová et al ., 2021 ).…”
supporting
confidence: 52%
“…Analysis of the results obtained with specimens of the B.1.1.7 lineage always revealed a notable difference between the Cq values for the N and S genes (mean, + 11 ±2; range, + 8/ + 15), while such a difference was not observed with specimens of the other lineages ( Table 1 ). The Taq-Path COVID-19 RT-PCR assay revealed a missing S-gene target amplification with all specimens of VOC-UK, but also with B.1.258 ( Table 1 ), as expected from the presence of the HV69-70 spike deletion also in members of this lineage ( Brejová et al ., 2021 ).…”
supporting
confidence: 52%
“…This variant was identified in the Czech Republic and Slovakia in late 2020, within the clade B.1.258 (Brejováet al, 2021). It has been observed to escape the immune response and increase the severity of infection.…”
Section: Lineage B1258dmentioning
confidence: 99%
“…A study in Slovakia found that samples with spike target failure were assigned as B.1.258. The B.1.258 lineage with the deletion had a higher viral load and became one of the dominant variants found in Slovakia [6]. The higher infectivity of variant harboring Δ69-70 mutation may be explained by the increased cleavage on S2 domain of spike protein with the mutation [7].…”
Section: Discussionmentioning
confidence: 99%